The evaluation of the subtropical crops extension and advisory service (Subtrop) as perceived by farmer members and extension advisors in the subtropical regions, South Africa - Terblanche, S.J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.